2010
DOI: 10.3109/09513590.2010.538099
|View full text |Cite
|
Sign up to set email alerts
|

d-Chiro-inositol and its significance in polycystic ovary syndrome: a systematic review

Abstract: Heterogeneity observed in the methodologies of each study, the scarcity of relevant studies and the small sample sizes used prohibit reliable conclusions to be drawn. Therefore, more studies must be conducted in the future to evaluate accurately the effects of DCI in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 20 publications
0
43
0
6
Order By: Relevance
“…Increasing evidence has demonstrated that myo-ins plays a key role in cell morphogenesis and cytogenesis, lipid synthesis, structure of cell membranes, and cell growth [10]. Myo-Ins administration improves hormonal profile, oocyte maturation, and insulin resistance; furthermore, it promotes the meiotic progression of germinal vesicle oocytes [11, 12]. Recent studies on PCOS patients showed a decrease of androgen levels and an improvement in ovulation and metabolic parameters after treatment with myo-ins and D-chiro-inositol (D-chiro-ins), which is another stereoisomeric form of inositol [13].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that myo-ins plays a key role in cell morphogenesis and cytogenesis, lipid synthesis, structure of cell membranes, and cell growth [10]. Myo-Ins administration improves hormonal profile, oocyte maturation, and insulin resistance; furthermore, it promotes the meiotic progression of germinal vesicle oocytes [11, 12]. Recent studies on PCOS patients showed a decrease of androgen levels and an improvement in ovulation and metabolic parameters after treatment with myo-ins and D-chiro-inositol (D-chiro-ins), which is another stereoisomeric form of inositol [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, authors suggested that the insulin resistance observed in PCOS women is related, at least partially, to the defect in one of the mediators of insulin containing D-chiro-inositol (Bromberg and Edlich, 1994[8]). Metformin ameliorates insulin action in PCOS patients through releasing D-chiro-inositol-IPG mediator (Galazis et al, 2011[24]). Myo-inositol is the most common form of inositol, which is converted to D-chiro-inositol by an epimerase (Larner, 2002[40]).…”
Section: Nutrients and Pcosmentioning
confidence: 99%
“…Nevertheless, myo-inositol potentially improves the metabolic profile, whereas D-chiro-inositol exerts positive effects on hyperandrogenism (Pizzo et al, 2014[60]). Yet, a systematic review assessing the effects of D-chiro-inositol on ovulation and/or metabolic markers in PCOS failed to find consistent conclusion, mostly because of heterogeneity in the method of each study and also lack of relevant trials and small sample sizes (Galazis et al, 2011[24]). Finally, Unfer et al (2012[76]) performed a meta-analysis of 6 randomized placebo-controlled trials which used a range of 0.2-4 g/day myo-inositol in PCOS patients and concluded that myo-inositol supplementation can decrease the levels of various hormones such as LH, LH/follicle stimulating hormone (FSH), PRL, and testosterone and improve the dyslipidemia by reducing insulin concentrations.…”
Section: Nutrients and Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by Vitagliano et al, despite the plethora of published papers about the treatment of PCOS with Inositol isoforms (for systematic reviews, see Unfer et al [3] and Galazis et al [4]), very few of them focused on lean patients (BMI \ 25).…”
Section: Dear Editormentioning
confidence: 99%